Diagnóstico da gestão em segurança e saúde do trabalho nas indústrias maquiladoras brasileiras instaladas no Paraguai - Gimenez, Juan Alberto Mongelos (2018)
In recent years trade relations between Brazil and Paraguay have increased. Under current economic conditions, the industry of this country is integrating itself into the production chains of the Brazilian industries, thus strengthening a productive integration. In this sense, the implementation of the Paraguayan regime of the export maquiladora industry stands out, which is a tax-exempt production model. Most of the Brazilian industrialists who are investing in this country choose the maquila regime, taking advantage of, besides the tax exemptions, the low costs of production and the local labor. This paper presents the results of a research carried out to obtain a diagnosis of the current state of work safety and health management in the Brazilian maquiladora industries installed in Paraguay. By means of an exploratory approach, field survey and with tools developed based on local legislation and the normative requirements of the OHSAS 18001 management system, a diagnosis of the situation was obtained, which shows low levels in the management practices consolidated by this as well as the lack of compliance with legislation by just over half of the companies. As a result of this, it is concluded that managerial occupational health and safety policies, with preventive objectives, are being neglected by companies. The paper also presents a summary of the main considerations of the diagnosis obtained.